ISOLATION AND IDENTIFICATION OF FLAVONOID COMPOUNDS ETHANOL EXTRACT OF SUANGGI LEMON PEEL Citrus limon L. - Rizya Marchilia Mamahit; Fatimawali Fatimawali; Meilani Jayanti (PHARMACON, 2023)
ABSTRACTSuanggi lemon peel is a plant that is often used as a traditional health therapy. The outer skin of the lemon suanggi (Citrus Limon L.) is rich in oil glands, bright yellow in color with a distinctive and fresh citrus aroma. The purpose of this study was to isolate and identify the class of flavonoid compounds from the rind of lemon suanggi (citrus limon L.) by using the UV-Vis spectrophotometer method. The rind of the suanggi lemon was extracted by maceration method using 95% ethanol as solvent which resulted in a thick extract of suanggi lemon rind. Isolation was carried out by thin layer chromatography (TLC) method with Chloroform: n-hexane (4:2) as the eluent. The fourth spot from the result of Thin Layer Chromatography was positive for containing flavonoid compounds. From the spectrum of the UV-Vis spectrophotometer, it can be assumed that the flavonoid compound is a flavonol group, which can be seen from its wavelength range, which is between 200- 500 nm from its wavelength range of 366 nm.Keywords: lemon suanggi, flavonoids, thin layer chromatography, UV-Vis spectrophotometer.